2019
DOI: 10.1111/cbdd.13605
|View full text |Cite
|
Sign up to set email alerts
|

Identification and molecular characterization of the tubulin‐podophyllotoxin‐type lignans binding site on Giardia lamblia

Abstract: There are several drugs for the treatment of giardiasis; however, there is a tendency for patients to abandon treatment because of drug‐related adverse effects, resulting in relapses, acquired resistance, and higher rates of treatment failure. Recently, we reported some podophyllotoxin‐type lignans from Bursera fagaroides var. fagaroides showing antigiardial activity. In the present work, we demonstrated that 5′‐desmethoxy‐peltatin‐A‐methylether (5‐DES), acetylpodophyllotoxin (APOD), and podophyllotoxin (POD) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…The same occurs with podophyllotoxin-type lignans from Bursera fagaroides var. fagaroides , which affect the distribution and staining pattern of microtubular structures on Giardia trophozoites, by the union in colchicine binding site ( Gutiérrez-Gutiérrez et al, 2017b ; Gutiérrez-Gutiérrez et al, 2019 ). On the other hand, it has been shown that paclitaxel is capable of producing microtubule stabilization, thereby generating a significant increase in the size of both the median body and the eight axonemes ( Dawson et al, 2007 ).…”
Section: Discussionmentioning
confidence: 99%
“…The same occurs with podophyllotoxin-type lignans from Bursera fagaroides var. fagaroides , which affect the distribution and staining pattern of microtubular structures on Giardia trophozoites, by the union in colchicine binding site ( Gutiérrez-Gutiérrez et al, 2017b ; Gutiérrez-Gutiérrez et al, 2019 ). On the other hand, it has been shown that paclitaxel is capable of producing microtubule stabilization, thereby generating a significant increase in the size of both the median body and the eight axonemes ( Dawson et al, 2007 ).…”
Section: Discussionmentioning
confidence: 99%
“…The lignans 1-19 have been isolated from specimens of B. fagaroides, collected in México, principally from the bark (Michoacán state) [19,20,26,27,38,39,41,42], two reports from Oaxaca state [25] and one from Guerrero state [42] analyzed the resin. The polarity of the used extracts was chloroform (CHCl 3 ) [25,26], dichloromethane (CH 2 Cl 2 ) [20,38,40,41], ethanol (CH 3 CH 2 OH) [27], CH 3 CH 2 OH 80% (previously treated with hexane) [42], and methanol (CH 3 OH) 70% [19,29,39]. In general, the purification of these extracts was carried out by bioassay-guided chromatographic methods [19].…”
Section: Isolation and Characterizationmentioning
confidence: 99%
“…More recently, the same research group demonstrated that 5′-desmethoxy-peltatin-A-methylether ( 3 ), acetylpodophyllotoxin ( 5 ), and podophyllotoxin ( 1 ) affect the pattern of microtubular structures on Giardia trophozoites. A docking study revealed that the lignans act via binding in a hydrophobic pocket in the heterodimer interface of tubulin in Giardia [ 41 ].…”
Section: Other Effectsmentioning
confidence: 99%